Answer:
![t = 0.875](https://tex.z-dn.net/?f=t%20%3D%200.875)
Step-by-step explanation:
Given
<u>Brand A</u> <u>Brand B</u>
![n_2 = 12](https://tex.z-dn.net/?f=n_2%20%3D%2012)
![\bar x_2 = 18.9](https://tex.z-dn.net/?f=%5Cbar%20x_2%20%3D%2018.9)
![\sigma_2 = 7.5](https://tex.z-dn.net/?f=%5Csigma_2%20%3D%207.5)
Required
Determine the test statistic (t)
This is calculated as:
![t = \frac{\bar x_1 - \bar x_2}{s\sqrt{\frac{1}{n_1} + \frac{1}{n_2}}}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B%5Cbar%20x_1%20-%20%5Cbar%20x_2%7D%7Bs%5Csqrt%7B%5Cfrac%7B1%7D%7Bn_1%7D%20%2B%20%20%5Cfrac%7B1%7D%7Bn_2%7D%7D%7D)
Calculate s using:
![s = \sqrt{\frac{(n_1-1)*\sigma_1^2+(n_2-1)*\sigma_2^2}{n_1+n_2-2}}](https://tex.z-dn.net/?f=s%20%3D%20%5Csqrt%7B%5Cfrac%7B%28n_1-1%29%2A%5Csigma_1%5E2%2B%28n_2-1%29%2A%5Csigma_2%5E2%7D%7Bn_1%2Bn_2-2%7D%7D)
The equation becomes:
![s = \sqrt{\frac{(12-1)*8.7^2+(12-1)*7.5^2}{12+12-2}}](https://tex.z-dn.net/?f=s%20%3D%20%5Csqrt%7B%5Cfrac%7B%2812-1%29%2A8.7%5E2%2B%2812-1%29%2A7.5%5E2%7D%7B12%2B12-2%7D%7D)
![s = \sqrt{\frac{1451.34}{22}}](https://tex.z-dn.net/?f=s%20%3D%20%5Csqrt%7B%5Cfrac%7B1451.34%7D%7B22%7D%7D)
![s = \sqrt{65.97}](https://tex.z-dn.net/?f=s%20%3D%20%5Csqrt%7B65.97%7D)
![s = 8.12](https://tex.z-dn.net/?f=s%20%3D%208.12)
So:
![t = \frac{\bar x_1 - \bar x_2}{s\sqrt{\frac{1}{n_1} + \frac{1}{n_2}}}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B%5Cbar%20x_1%20-%20%5Cbar%20x_2%7D%7Bs%5Csqrt%7B%5Cfrac%7B1%7D%7Bn_1%7D%20%2B%20%20%5Cfrac%7B1%7D%7Bn_2%7D%7D%7D)
![t = \frac{21.8 - 18.9}{8.12 * \sqrt{\frac{1}{12} + \frac{1}{12}}}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B21.8%20-%2018.9%7D%7B8.12%20%2A%20%5Csqrt%7B%5Cfrac%7B1%7D%7B12%7D%20%2B%20%5Cfrac%7B1%7D%7B12%7D%7D%7D)
![t = \frac{21.8 - 18.9}{8.12 * \sqrt{\frac{1}{6}}}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B21.8%20-%2018.9%7D%7B8.12%20%2A%20%5Csqrt%7B%5Cfrac%7B1%7D%7B6%7D%7D%7D)
![t = \frac{21.8 - 18.9}{8.12 * 0.408}}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B21.8%20-%2018.9%7D%7B8.12%20%2A%200.408%7D%7D)
![t = \frac{2.9}{3.31296}}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B2.9%7D%7B3.31296%7D%7D)
![t = 0.875](https://tex.z-dn.net/?f=t%20%3D%200.875)
amount after 2 years = 6000(1 + (0.04/12))^24 = 6498.86
Answer: A
Step-by-step explanation:
Answer:
Step-by-step explanation:
x=0 y=6-2*0=6
x=1 y=6-2*1=4
x=2 y=6-2*2=2
x=3 y=6-2*3=0
6-2x=3
-6 -6
-2x=-3
2x=3
:2 :2
x=3/2
x=1.5